Strategi pemanfaatan moluska sebagai pangan lokal untuk mendukung produktivitas komoditas perikanan menunjang ekowisata dan ekonomi masyarakat di Keakwa, Timika - Surbakti, Suriani; Sufaati, Supeni; Bangun, Sesharefi E.A.; Baticaca, Fransisca B.; Tingginehe, Rosmin M.; Yembise, Yohana S. (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
Keakwa village is located in the coastal mangrove forest area in East Central Mimika District with an area of 9,052.5 ha. The Keakwa mangrove forest is a mangrove forest that grows abundantly to protect coastlines and residential areas. The Mollusk Group in Keakwa has the potential as a source of protein and economic and cultural value for the community. through Lectures and Focus Group Discussion activities for the Keakwa community, activities carried out for 2 weeks in 2022. utilizing mollusks around Keakwa waters. These conditions can be developed as ecotourism potential. This service aims to understand and get to know molluscs and their use and prospects as a source of community economy in Keakwa, Timika, strategies for developing and utilizing molluscs in ecotourism development, by conducting lectures, from the results of evaluating knowledge about the benefits and potential of local resources, especially molluscs, after Community outreach is carried out to understand the benefits and potential of local resources. With the hope of supporting the development and management initiatives of the Keakwa community in the field of ecotourism development, in supporting the economy of the Keakwa community.